2000
DOI: 10.1042/0264-6021:3460163
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Leishmania major dUTP nucleotidohydrolase, a distinct nucleotide-hydrolysing enzyme in kinetoplastids

Abstract: We have previously reported the presence, in the parasitic protozoan Leishmania major, of an enzyme involved in controlling intracellular dUTP levels. The gene encoding this enzyme has now been overexpressed in Escherichia coli, and the recombinant enzyme was purified to homogeneity. Biochemical and enzymic analyses of the Leishmania enzyme show that it is a novel nucleotidohydrolase highly specific for deoxyuridine 5'-triphosphate. The enzyme has proved to be a dimer by gel filtration and is able to hydrolyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…These enzymes act as dimers and are able to hydrolyze not only dUTP but also dUDP (15), whereas dUDP has been shown to be an inhibitor of the trimeric enzyme in E. coli (16). They are, in addition, subject to product inhibition by dUMP (17). The structure of TcdUTPase revealed a dimeric all ␣-helical structure that is very distinct from the trimeric enzymes (18), with which they share no sequence similarity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These enzymes act as dimers and are able to hydrolyze not only dUTP but also dUDP (15), whereas dUDP has been shown to be an inhibitor of the trimeric enzyme in E. coli (16). They are, in addition, subject to product inhibition by dUMP (17). The structure of TcdUTPase revealed a dimeric all ␣-helical structure that is very distinct from the trimeric enzymes (18), with which they share no sequence similarity.…”
mentioning
confidence: 99%
“…The metals were implicated in substrate binding and led to the proposal that these dimeric dUTPases utilize a mechanism of reaction similar to that used in the phosphoryl transfer reactions catalyzed by DNA polymerases (20,21). Indeed, the dimeric enzyme, like the trimeric one, requires divalent metal ions for activity (17).…”
mentioning
confidence: 99%
“…Kinetic characterization of these novel forms of dUTPases showed that they accepted either dUDP or dUTP as a substrate, whereas the dUMP product was found to be their potent inhibitor, which clearly indicated the distinct mode of action of these enzymes [88,93]. The first dimer dUTPase structure (Trypanosoma cruzi dUTPase) revealed many structural and mechanistic aspects [94].…”
Section: Dimeric Dutpasementioning
confidence: 99%
“…A group of dUTPases has been shown to form homodimers in solution and possess sequence conservation that is different from the monomeric or trimeric dUTPases [88]. These results, combined with phylogenetic analysis, allowed the definition of a new superfamily of d(C/U)TPases [36], including several distinct enzyme families (dUTPases in trypanosomatides, Campylobacter jejuni and dCTP/dUTPases in some Gram-negative bacteria and T4-like phages, as well as dUTPases in various Gram-positive bacteria and their phages) [89][90][91].…”
Section: Dimeric Dutpasementioning
confidence: 99%
“…The soluble crude extract was obtained by sonication and centrifugation at 11000xg. The purification protocol developed consisted in three chromatographic steps (Table I), hydroxyapatite, anion exchange chromatography in DEAE-cellulose, and mono-Q chromatography as previously described for dimeric enzymes [15,16]. This protocol gives 20 mg of protein per liter of culture and the protein is more than 95% free of impurities as judged by SDS-PAGE analysis with Coomassie blue staining of overloaded gels.…”
Section: Overexpression Of Recombinant Dutpase Of C Jejunimentioning
confidence: 99%